Factors that Influence Mobile Bully-victim Behaviour on Mobile Social Networks: The Case of Facebook - Ndyave, Zizipho (Department of Information Systems, 2022)
Mobile bullying on social networks is a growing problem in South African public high schools. It is described as a fairly new form of cyber bullying which is conducted using a mobile phone through communication channels such as text messages, emails, Instant messaging and other chat rooms such as social networks. Excessive usage of mobile phones in schools has elevated the delinquency of bullying in school grounds and challenged how school policies are executed when it comes to mobile bullying. While mobile technology is more widely use than conventional methods to commit antisocial behaviours today, our understanding of mobile bullying is still limited in the South African context. Although studies on bullying in general have been conducted, there has been limited focus on one type called bully-victims. Bully-victims are adolescents that swing between being a bully and a victim and are difficult to identify. The present study aims to bridge the gap by examining the factors that influence the behaviour of mobile bully-victims on Facebook in South African public secondary schools. Children who are greatly exposed to violence and victimisation at an early age tend to struggle when they become adults and experience emotional trauma, perform poorly in their academics and at times commit suicide. Cyberbullying has similar negative impacts whereby the intention is to frequently harm another person using virtual platforms. Research shows that there is rapid growth in suicidal cases which is one of the leading causes of death among adolescents in South Africa. While suicide has not been associated with bully-victims in South Africa, international studies link adolescent suicidal tendencies with bully-victim behaviour. Facebook has been chosen because it is the most popular and commonly use social network by adolescents. Extensive literature on the potential causes of mobile bully-victim behaviour has been reviewed and a conceptual model (Mobile Bully-victim Model) of the influencing factors identified. This model aims at assisting schools understand the nature of mobile bully-victims, potential causes of bully-victim behaviour and guide the development of appropriate interventions for this form of aggression. A total number of 457 school learners participated on the quantitative survey both from Gauteng and Western Cape provinces. The study population is based on learners from Western Cape and Gauteng public schools because there are more school violence cases occurring in communities where there is a high crime rate. These two provinces fall under four provinces including Limpopo and Free State that are leading in high crime rate in South Africa. Due to unavailability to participate from other provinces, only Western Cape and Gauteng public schools were available and willing to participate in the study. 319 of those learners were found to be mobile bully-victims. The degree to which mobile bully-victim behaviour occur was examined in relation to Anonymity, Collective behaviour, Power, Facebook usage and Emojis and Facebook features. After various tests including spearman correlation, T-tests, and regression analysis were run, the results confirmed that adolescents who have anonymous profiles that follow collective behaviour of public pages, possess power and who are frequent Facebook users are likely to be mobile bully-victims and they demonstrate bully-victim behaviour on Facebook. However, Emoji and features showed an inverse relationship with bully-victim behaviour on Facebook. Therefore, the study confirms that these factors do indeed influence mobile bully-victim behaviour on Facebook except for Emoji and Facebook features.